ChemInform Abstract: 2‐Aminobenzimidazole Organocatalyzed Asymmetric Amination of Cyclic 1, 3‐Dicarbonyl Compounds. Issue 22 (15th May 2015) - Trillo, Paz; Gomez‐Martinez, Melania; Alonso, Diego A.; Baeza, Alejandro
Abstract: In contrast to cyclic 1, 3‐dicarbonyl compounds, which are aminated in high yields and with low to good enantioselectivities, acyclic derivatives afford racemic mixtures.